Uma experiência na Educação de Jovens e Adultos: Aprendizados e desafios - Rossi, Rafael; Rossi, Aline Cristina Santana [UNESP] (My University, 2015)
The literacy process with adults and elderly imposes a series of challenges to educators who wish to go beyond the word to discuss with them the life and the world itself. So in this article we present experience developed within the Youth and Adult Education Program - PEJA - in Presidente Prudente-SP, in order to share lessons learned and difficulties that much helped us in building an introductory methodological reflection to literacywith the political and pedagogical contribution of the Paulo Freirés thought.
An experience in youth and adult education: Learning and challenges
Keywords: Education for youth and adults; Literacy; PEJA; Teaching commitment